Split second [videorecording (DVD)] - Thompson, Gary Scott; Hauer, Rutger, 1944-2019; Cattrall, Kim; Duncan, Alastair, 1958-; Pollard, Michael J. (MVD Rewind, 2020)
In the year 2008, the cops are better armed than before, but nothing has prepared them for this. Swift, sharp-clawed and deadly, something moves among them tearing out human hearts and devouring them. Maverick cop Harley Stone lost his partner to the beast, and now it looks like his girlfriend Michelle is next on the killer's list. Teamed with a rookie detective, Stone must stalk the edge of his sanity if he is to destroy the rampaging Evil on the outside and banish the very real demons within.